Manajemen Pembelajaran Pendidikan Agama Islam Berbasis Teknologi Informasi dan Komunikasi di Madrasah Tsanawiyah Negeri Ciledug - Asep - Kurniawan (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
In the era of globalization and the rapid development of Information and Communication Technology (ICT), it is urgent that all education systems and models adapt and adopt this ICT for better quality education. This article was aimed at analyzing ICT-based Islamic Education Learning at Public Junior High School Ciledug. This article was based on the assumption that integrating many subjects with ICT, which in this case was ICT, was very important to be applied in this digital era. There were some obstacles, however,Â  were faced by many educational institutions such as not having a clear design in utilizing ICT in an effort to combine the two scientific fields. The article was the result of qualitative research with a descriptive method. Data collection techniques were taken through observation, interviews and documentation studies. The data analysis adopted the analysis of Miles and Huberman. The results showed that ICT-based Islamic Education Learning that could be applied at Public Islamic Junior High School Ciledug through the process of planning, selecting media and materials, and doing evaluations. Other learning materials and facilities were designed in a computer program. Through this model the teacher acted as a facilitator and motivator of learning for students and provided reinforcement of materials that required explanation among students.